Detection of Exhaled Volatile Organic Compounds Improved by Hollow Nanocages of Layered Double Hydroxide on Ag Nanowires. (30th September 2019) - Qiao, Xuezhi; Chen, Xiangyu; Huang, Chuanhui; Li, Ailin; Li, Xiao; Lu, Zhili; Wang, Tie
Abstract: To detect biomarkers from human exhalation, air flow dynamics on the nanoparticle surface were explored by a surface‐enhanced Raman scattering (SERS) sensor. A hollow Co‐Ni layered double hydroxide (LDH) nanocage on Ag nanowires (Ag@LDH) was prepared. Ag nanowires provided amplified Raman signals for trace determination; hollow LDH nanocages served as the gaseous confinement cavity to improve capture and adsorption of gaseous analytes. The Raman intensity and logarithmic analyte concentration exhibit an approximately linear relationship; the detection limit of SERS sensors for aldehyde is 1.9×10 −9 v/v (1.9 ppb). Various aldehydes in mixed mimetic gas are distinguished by Raman spectra statistical analysis assisted by multivariate methods, including principal component analysis and hierarchical cluster analysis. The information was recorded in a barcode, which can be used for the design and development of a desktop SERS sensor analysis system for large‐scale lung cancer detection. Abstract : Ein SERS‐Mikrosensor ermöglicht den Nachweis flüchtiger organischer Aldehyde. Die integrierte Information bezüglich der Gas‐Spezies wird in einem Barcode erfasst, der von einer dritten Komponente schnell, komfortabel und präzise ausgelesen werden kann.